2017
DOI: 10.1111/mcn.12492
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the effects of intrapartum factors, neonatal characteristics, and skin‐to‐skin contact on early breastfeeding initiation

Abstract: This study aims to determine relationships between intrapartum factors, neonatal characteristics, skin-to-skin contact (SSC), and early breastfeeding initiation after spontaneous vaginal and Caesarean section or operative vaginal birth. A total of 915 mother-newborn dyads were considered in a hypothetical model based on integrated concepts of breastfeeding initiation model, infant learning framework, and attachment theory. Multiple-group path analysis was used to determine whether differences exist between eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
2
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 70 publications
(149 reference statements)
2
49
2
15
Order By: Relevance
“…Four studies defined SSC as the placing of the naked baby on the mother’s chest or abdomen [ 14 , 16 , 18 , 19 ], whereas another study allowed the baby to wear cap, diaper and socks [ 13 ]. Two studies mentioned in their definition of SSC that both the mother and the infant need to be covered with a warm blanket or dry towel to stabilise the infant [ 17 , 18 ] Four studies explained in their definitions of SSC, that the newborn infant’s position should be placed prone on the mother’s bare chest or abdomen [ 16 , 18 20 ]. Three other studies stated the time that the newborn infant stayed SSC with the mother for 30 minutes [ 16 ], first hour [ 11 ] or two hours [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies defined SSC as the placing of the naked baby on the mother’s chest or abdomen [ 14 , 16 , 18 , 19 ], whereas another study allowed the baby to wear cap, diaper and socks [ 13 ]. Two studies mentioned in their definition of SSC that both the mother and the infant need to be covered with a warm blanket or dry towel to stabilise the infant [ 17 , 18 ] Four studies explained in their definitions of SSC, that the newborn infant’s position should be placed prone on the mother’s bare chest or abdomen [ 16 , 18 20 ]. Three other studies stated the time that the newborn infant stayed SSC with the mother for 30 minutes [ 16 ], first hour [ 11 ] or two hours [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Few mothers in Kathmandu Valley reported holding their infant immediately after giving birth, which in this study served as a proxy for skin‐to‐skin contact between newborn and mother. Immediate skin‐to‐skin contact is a powerful covariate of early breastfeeding initiation and successful exclusive breastfeeding (Lau et al, ). Delaying this first skin‐to‐skin contact may contribute to breastfeeding difficulty and the provision of supplemental or replacement feeds of BMS soon after birth in Kathmandu Valley delivery facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Early initiation of breastfeeding can reduce both neonatal and early infant mortality [31][32][33] . Many factors are associated with early breastfeeding initiation, and skin-to-skin contact and health education have been proven effectively [34][35][36] . A recent review from the US concluded that baby-friendly practices can help increase prevalence of EIBF and EBF [37] .…”
Section: Discussionmentioning
confidence: 99%